Negociações coletivas na indústria automotiva goiana - Amorim, Inara Rosa de (2011)
This work aims to analyze the course of collective negotiations of car manufacturers installed in the State of Goiás. The discussion was framed by a broad debate of the collective labor negotiations in Brazil, under the influence of major changes in the labor legislation as well as the movement of expansion and "devolution" of the area of automotive industry in Brazil. Fundamentally, we interpreted the collective labor agreements signed between Mitsubishi Motors Corporation of Brazil (MMC) and the Sindicato dos Trabalhadores nas Indústrias Metalúrgicas Mecânicas e Material Elétrico de Catalão (SIMECAT), and also collective work agreements between the Sindicato dos Trabalhadores nas Indústrias Metalúrgicas Mecânicas e Material Elétrico de Anápolis (SindMetana) and the Sindicato das Indústrias Metalúrgicas Mecânicas e Material Elétrico de Anápolis (Simea), which regulate labor relations in Hyundai Motors Brazil. The analysis of the collective instruments that make up the data body of this research was based on classification schemes of collective clauses according to the thematic scope proposed by Horn (2003). The author s methodology also enables that the classified clauses be compared to the current Brazilian legislation. From the data interpretation it was possible to elucidate relevant issues, namely: how the union representation in the above-mentioned towns was built and its impact on the negotiations; which have been the changes in the thematic scope of collective instruments over the years; if the instruments were able to create additional provisions in relation to the extensive legislation governing employment relations in Brazil; and which are the main similarities and differences between the collective instruments in these production units. It was possible to notice that the negotiating experience of the Anápolis s unions, as well as the unions ammount of years of work, did not translate into a higher standard of regulation of the employment relationship. By contrast, the SIMECAT unionists led by young and inexperienced members has proved, since its establishment, to be tightly linked to the interests of the MMC employees. Therefore, we could observe a greater work regulation to workers of the Catalão automotive industry in relation to Hyundai s employees.